2012
DOI: 10.1103/physrevc.86.014310
|View full text |Cite
|
Sign up to set email alerts
|

Beyond-mean-field study of the possible “bubble” structure of34Si

Abstract: Recent self-consistent mean-field calculations predict a substantial depletion of the proton density in the interior of 34 Si. In the present study, we investigate how correlations beyond the mean field modify this finding. The framework of the calculation is a particle-number and angularmomentum projected Generator Coordinate Method based on Hartree-Fock-Bogoliubov+Lipkin-Nogami states with axial quadrupole deformation. The parametrization SLy4 of the Skyrme energy density functional is used together with a d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
81
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 70 publications
8
81
2
Order By: Relevance
“…The isovector contribution is, of course, also responsible for the difference between the effective proton and neutron single-particle potentials, while the radial (density) profiles depend on the shell structure of occupied orbitals in the self-consistent solution for a particular nucleus. In this respect, especially interesting is the case of 34 Si, for which a possible central depletion of the proton density distribution has been analysed using a variety of theoretical approaches [26,27], and experimental constraints on the strength of the two-body spin-orbit interaction have been reported [15,28]. For the effective interaction DD-MEδ that explicitly includes contributions from both ρ and δ meson exchange in the direct term, the isovector channel of the spin-orbit potential is enhanced when compared to DD-ME2, although in both models the total isovector part of the spin-orbit potential is an order of magnitude weaker than the isoscalar contribution [20].…”
Section: Resultsmentioning
confidence: 99%
“…The isovector contribution is, of course, also responsible for the difference between the effective proton and neutron single-particle potentials, while the radial (density) profiles depend on the shell structure of occupied orbitals in the self-consistent solution for a particular nucleus. In this respect, especially interesting is the case of 34 Si, for which a possible central depletion of the proton density distribution has been analysed using a variety of theoretical approaches [26,27], and experimental constraints on the strength of the two-body spin-orbit interaction have been reported [15,28]. For the effective interaction DD-MEδ that explicitly includes contributions from both ρ and δ meson exchange in the direct term, the isovector channel of the spin-orbit potential is enhanced when compared to DD-ME2, although in both models the total isovector part of the spin-orbit potential is an order of magnitude weaker than the isoscalar contribution [20].…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been difficult to measure charge densities at the center of unstable nuclei, the new technology such as SCRIT [19] could open a way to observe such proton bubble structure. It is noted that correlations beyond MF tend to quench the bubble, as shown for 34 Si by a recent study using the generator-coordinate method (GCM) [20]. Since the wave function of the GCM ground state was found spread over a wide range of intrinsic deformations, it was shown that the level occupation was smeared over the Fermi energy and the p1s 1/2 orbital was partially occupied.…”
mentioning
confidence: 88%
“…These correlations reduce the depletion of the proton density. However, the transition strengths ρ 2 (E0; 0 [20] compared to the experimental value [21]. This discrepancy might indicate that the two lowest 0 + GCM states are too strongly mixed in the calculations of Ref.…”
mentioning
confidence: 89%
“…Theoretically, a (semi-)bubble structure can exist in many nuclei, ranging from intermediatemass isotopes to hyperheavy systems, including 34 Si [9][10][11], 44 S [12], 46 Ar [12,13], neutron-rich Ar isotopes around 68 Ar [13], 36 Ar and Hg isotopes [3][4][5], superheavy and hyperheavy isotopes [14][15][16][17], etc. Some of these candidates, such as 36 Ar and Hg isotopes, have been ruled out by experiments [18]. However, other candidates are still standing.…”
Section: Introductionmentioning
confidence: 99%
“…A. Wheeler [2] prior to 1950s. The bubble structure is one of the simplest but widely discussed topology structure in history [3][4][5][6][7][8], and it is still a hot topic both theoretically and experimentally in recent years [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. However, a bubble structure is not expected to exist in nuclei because the nature of nucleon-nucleon interaction will lead to a saturation density (ρ sat ∼ 0.16 fm −3 ) at the center of nucleus.…”
Section: Introductionmentioning
confidence: 99%